Effect of physostigmine on recovery from septic shock following intra-abdominal infection - Results from a randomized, double-blind, placebo-controlled, monocentric pilot trial (Anticholium® per Se) - Pinder, Nadine; Bruckner, Thomas; Lehmann, Monika; Motsch, Johann; Brenner, Thorsten; Larmann, Jan; Knebel, Phillip; Hoppe-Tichy, Torsten; Swoboda, Stefanie; Weigand, Markus A.; Hofer, Stefan; Zimmermann, Johannes B. (Journal of critical care, 2019)
Purpose - The cholinergic anti-inflammatory pathway has been shown to be accessible by physostigmine salicylate in animal models. However, the cholinesterase inhibitor is not approved for adjunctive therapy in sepsis, and tolerability and safety of high initial doses followed by continuous infusion have not been investigated. - Materials and methods - In this trial, 20 patients with perioperative septic shock due to intra-abdominal infection were eligible. The physostigmine group received an initial dose of 0.04mg/kg physostigmine salicylate, followed by continuous infusion of 1mg/h for 120h; the placebo group was treated with 0.9% sodium chloride. Primary outcome was the mean Sequential Organ Failure Assessment (SOFA) score during treatment and up to 14days. - Results - Administration of physostigmine salicylate was well tolerated. Mean SOFA scores were 8.9±2.5 and 11.3±3.6 (mean±SD) for physostigmine and placebo group, respectively. Adjusted for age, difference between means was not statistically significant (−2.37, 95% CI: −5.43 to 0.70, p=0.121). Norepinephrine doses required only appeared lower in the physostigmine group (p=0.064), along with a more rapid reduction from an elevated heart rate possibly indicating less hemodynamic instability. - Conclusions - Treatment with physostigmine salicylate was feasible and safe. Further studies are justified to assess the effect on recovery from septic shock. - Trial registration - EudraCT Number 2012-001650-26, ClinicalTrials.gov identifier NCT03013322.